Measuring and valuing convenience and service quality: A review of global practices and challenges from mass transit operators and railway industries - Richard Anderson; Benjamin Condry; Nicholas Findlay; Ruben Brage-Ardao; Haojie Li (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
Origin-destination demand, trip patterns, pricing and transport networks alone cannot explain passenger demand for public transport modes. Other factors of convenience and service quality play a key role in influencing demand and mode choice but they are often more complex and harder to define, measure and value. This paper argues that the good measurement of public transport convenience and service quality is a pre-requisite to its valuation and ensuring more optimal policy and management actions to minimise passengers' generalised time. The paper focusses necessarily on the urban public transport operator and its measurement of service quality. We review the practical experience gained from over 20 years of international benchmarking with more than 50 metro, bus and suburban rail operators in large cities around the world. Specifically, we review the current standards and practices from the urban railway industry in measuring service quality and provide examples of how such performance in metro operations varies globally. It is demonstrated that current practice in many cities remains too operationally based, despite there being an opportunity for much more customer focused measures of service quality using the greatly increased data availability from new technologies. The experience of the UK railway industry in valuing convenience and service quality is discussed. Here, a common framework for demand forecasting has been developed combining service quality and convenience measures with other service attributes to effectively measure the 'attractiveness' of the service to customers. The paper concludes by considering the implications and opportunities for public transport operators, authorities and regulators worldwide in better measuring, valuing and managing public transport convenience in order to better meet mobility needs.
Keywords: 330